Short-chain polyglycerol production via microwave-assisted solventless glycerol polymerization process over lioh-modified aluminium pillared clay catalyst: Parametric study - Sajid, M. (MDPI AG, 2020)
In the current study, microwave-assisted glycerol polymerization for short-chain polyglycerol production was conducted unprecedentedly over low-cost catalyst, lithium-modified aluminium pillared clay (Li/AlPC) catalysts without the solvent. The influences of disparate reaction parameters such as the effects of Li loadings (10, 20, 30 wt. ), catalyst loadings (2, 3, 4 wt. ), operating temperatures (200, 220, 240 °C) and operating times (1-4 h) on the glycerol conversions, and polyglycerol yield (particularly for diglycerol and triglycerol), were elucidated. The fresh catalysts were subjected to physicochemical properties evaluation via characterization techniques, viz. N2 physisorption, XRD, SEM, NH3-TPD and CO2-TPD. In comparison, 20 wt. Li/AlPC demonstrated the best performance under non-conventional heating, credited to its outstanding textural properties (an increase of basal spacing to 21 A?, high surface area of 95.48 m2/g, total basicity of 34.48 mmol/g and average pore diameter of 19.21 nm). Within the studied ranges, the highest glycerol conversion (98.85) and polyglycerol yield (90.46) were achieved when catalyst loading of 3 wt. , reaction temperature of 220 °C and reaction time of 3 h were adopted. The results obtained also anticipated the higher energy efficiency of microwave-assisted polymerization than conventional technique (<8 h), as the reaction time for the former technology was shorter to attain the highest product yield. The study performed could potentially conduce the wise utilization of surplus glycerol generated from the biodiesel industry. © 2020 by the authors.